Strategi Komunikasi Synchronous-Asynchronous Guru Sekolah Dasar dalam Pembelajaran Daring Pandemi COVID-19 - I Putu Yoga Purandina; I Nyoman Buda Asmara Putra (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2021)
Teacher communication is one of the determinants of the effectiveness on bold learning during the COVID-19 pandemic. In bold learning, the teacher designs learning through two types according to the application/learning platform used. Thus, this study analyzes the teacher's synchronous and asynchronous strategies in the learning applications used. The subjects of this study were teachers of SD Negeri 1 and 7 Kediri, Tabanan which consisted of 4 (four) 4th, 5th, and 6th grade teachers on social studies material which was carried out randomly. Teachers of SD Negeri 1 & 7 Kediri Tabanan. The instruments used are observation sheets and interview lists. The results obtained are the establishment of synchronous and asynchronous communication according to the learning context and student conditions through the selection of appropriate learning platform applications. Communication strategies are built to streamline online learning so that online learning can motivate teachers and students.